al-Dilalah al-Siyaqiyyah Wa Suwar Tatbiquha Fi Tafsir al-Kasysyaf - Anas, Hazuar (ARABIYATUNA : Jurnal Bahasa Arab, 2017)
The significance is a science that studies meaning or linguistics that deals with the theory of meaning. There are several theories related to the issue of meaning: indicative and photographic theory, behavioral theory, contextual theory, analytic theory, and semantic field theory. This research is based on contextual theory. The issue of meaning in the owners of this theory is to use the language, the study of the meanings of words in this theory requires an analysis of the contexts and attitudes that are contained in them even if they were non-language. In addition, the researcher determines in this research the linguistic context, not all of the research on the context. The objectives of this research are a statement of the contextual meanings and types of application in the interpretation of the first volume scout. This research is a kind of qualitative research and uses the researcher in this researcher descriptive approach, which is the data and description of the data in sentences or words. The researcher asks for these data from the sources related to the subject of this research such as the book of interpretation of the Scouts and the books of semantics and the book, which looked for the application of semantics. This research is also called research desk. The results of this research are that the meanings of contextual interpretation of the Scout Volume I of the twenty places of the verses. The meaning of the word sedition, the book, today, and the beating